Biodegradation of aniline by freely suspended and immobilized Pseudomonas moraviensis AN-5 - Duc, Ha Danh; Triet, Bui Minh (Academia Journal of Biology, 2017)
Pseudomonas moraviensis AN-5 isolated from contaminated sludge could utilize aniline as a sole carbon and nitrogen source. The aniline degradation by cells immobilized in alginate, polyvinyl alcohol (PVA) and polyurethane foam (PUF) was significantly better than freely suspended cells. The immobilized AN-5 degraded aniline nearly completely at the initial concentration of 22 mM by 48 hr of incubation. Compared to other binding materials, PUF-immobilized cells were more stable in aniline biodegradation in reused cycles. Moreover, immobilized cells could be stored for three months at 4oC with little reduction of the aniline degradation capacity. These results revealed that PUF-immobilized P. moraviensis AN-5cells has enhanced aniline biodegradation activity.   Citation: Ha Danh Duc, Bui Minh Triet, 2017. Biodegradation of aniline by freely suspended and immobilized Pseudomonas moraviensis AN-5. Tap chi Sinh hoc, 39(3): 303-308. DOI: 10.15625/0866-7160/v39n3.9630. *Corresponding author: hadanhduc@gmail.com Received 11 April 2017, accepted 20 August 2017